A prática psicológica com famílias: problematizando a prática no contexto de clínicas-escola. - Leite, Danielle de Fátima da Cunha Cavalcanti de Siqueira (2016)
This thesis is a result of the doctoral candidate's questionings from experiences attending children and their families in many contexts. The goal of this thesis is problematizing the psychological practice of families that have attended college-clinics in Pernambuco. I order that, the following activities were done: analysis of eighty seven patient's records from three college-clinics; narrative interviews with four supervisor-professors and one psychology technician; and conversation groups made-up of sixteen students enrolled in Curricular Practical Trainings (CPTs) or extension programs. The main question that guided these activities was the questioning of the psychology practice with families. As an epistemological approach to analyze this phenomenon, the Gadamer’s Hermeneutics was assumed and, as presuppositions, the Existential Phenomenology of Heidegger and the Philosophical Hermeneutics of Gadamer were followed. In this context, the limitations of the technical language for patient records elaboration and clinical experience appropriation were demonstrated; the insufficiency of the hegemony of the technical-scientific model that guides the traditional psychology was observed, specially in psychology practices with families; some modalities of psychological practices that have been used to attend families in some of the college-clinics in Pernambuco were discussed and specific details of this clinic practice were unveiled. Given these discoveries, in the last part of this thesis, the author proposes another way for family-based psychological practices with the existential hermeneutical presuppositions. Taking this direction, the psychological practice with families cannot be analyzed exclusively through a technical model but through singular-plural roles that constitute a family. This horizon path requires recognition that nothing could be guaranteed in this way, but it points out the necessity that the family members have to assume an attitude of questioning, and dialogue to frequently. The objective of this attitude is to empower them not only to-be-who-they-are-among-others but also to act differently, without changing their own nature. With this perspective, the psychologist has to assume a posture of anticipating preoccupation so that the understandings and comprehensions collected would permit identification each singular-plural role and conduct them to new relationship possibilities.